The Global Integrated World Ocean Assessment: Linking Observations to Science and Policy Across Multiple Scales - Evans, Karen; Chiba, Sanae; Bebianno, Maria J.; Garcia-Soto, Carlos; Ojaveer, Henn; Park, Chul; Ruwa, Renison; Simcock, Alan J.; Vu, C. T.; Zielinski, Tymon (Frontiers in Marine Science, 2019)
In 2004, the United Nations (UN) General Assembly approved a regular process to report on the environmental, economic and social aspects of the world’s ocean. The Regular Process for Global Reporting and Assessment of the State of the Marine Environment, including Socioeconomic Aspects produced the first global integrated assessment of the marine environment in December 2016 (known as the first World Ocean Assessment). The second assessment, to be delivered in December 2020, will build on the baselines included in the first assessment, with a focus on establishing trends in the marine environment with relevance to global reporting needs such as those associated with the UN Sustainable Development Goals. Central to the assessment process and its outputs are two components. First, is the utilisation of ocean observation and monitoring outputs and research to temporally assess physical, chemical, biological, social, economic and cultural components of coastal and marine environments to establish their current state, impacts currently affecting coastal and marine environments, responses to those impacts and associated ongoing trends. Second, is the knowledge brokering of ocean observations and associated research to provide key information that can be utilised and applied to address management and policy needs at local, regional and global scales. Through identifying both knowledge gaps and capacity needs, the assessment process also provides direction to policy makers for the future development and deployment of sustained observation systems that are required for enhancing knowledge and supporting national aspirations associated with the sustainable development of coastal and marine ecosystems. Input from the ocean observation community, managers and policy makers is critical for ensuring that the vital information required for supporting the science policy interface objectives of the Regular Process is included in the assessment. This community white paper discusses developments in linking ocean observations and science with policy achieved as part of the assessment process, and those required for providing strategic linkages into the future.